DEPOSITIONAL ENVIRONMENT OF THE TERTIARY KERRI – KERRI FORMATION IN THE GONGOLA SUB-BASIN, NORTHERN BENUE TROUGH: PEBBLES MORPHOMETRIC AND GRAIN SIZE ANALYSIS APPROACH - ABUBAKAR, U.; MUSA, S.; TABALE, R. P.; YELWA, N. A.; IKECHUKWU, J. U.; USMAN, A. U.; USMAN, M. B.; ABUBAKAR, M. B.; SULAIMAN, A.; OLASEHINDE, A.; YUSUF, A.; MUKKAFA, S.; et al. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Pebbles have been reported in the Sandstones units of the Kerri - Kerri Formation, but their application as a tool for interpreting the depositional environment is limited. In this context, 510 quartz pebbles and 16 sandstone samples were collected for pebble morphometric and grain size analyses in order to assess the depositional environment of the formation. For the pebble morphometric study, the long (L), intermediate (I), and short (C) axes of each pebble were measured. For each pebble, four geometrical parameters related to depositional environmental studies were computed, these are: Maximum Projection Sphericity, Oblate Prolate Index, Coefficient of Flatness, and Disk - Road - Index. The standard sieving method was used to sieve the sandstone samples. Mean grain size (Mz), sorting (I), skewness (SKI), and kurtosis (KG) were determined as statistical parameters of the grain size. The mean value of the computed pebble shape parameters for the pebbles of the Kerri – Kerri Formation indicates that the pebbles were deposited in a fluvial environment. Based on the grain size analysis, the sediments were deposited by fluvial action with moderate to low energy of deposition setting closer to the source of the sediments. The bivariate plots show that all the pebbles and sandstone samples lie clearlywithin the river field, which suggests fluvial origin